Probuditi! - Van Allsburg, Chris (Houghton Mifflin Company, 2006)
On his birthday, Calvin and his friend Rodney see a magician perform, then copy him by hypnotizing Calvin's little sister, but the joke is on them when they are unable to snap her out of it.